Social Research Methods and Methodologies - Dhobi, Saleem (Patan Prospective Journal, 2023)
This article examines the methods and methods of social research. Social research is an activity carried out to search for explanations of a particular social situation. This article involves systematic data collection to understand patterns and changes in social conditions. The purpose of social research as a project is to transform the researcher's social science knowledge into social science skills. Social research, in-depth interviews, participant observation, non-participant observation, focus group discussions, case studies, grounded theory, etc. are some of the data collection methods in social research. The paper describes the nature of the study, theoretical stance, and research design including action research, naturalistic research, and ethnographic research, research design, interpretation, and ethical considerations. In this article, we considered case studies and participant observation as more reliable methods than other methods. Direct involvement of researchers in the subject area increases the level of reliability and usefulness of data in social research.